2002
DOI: 10.1002/pros.10122
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces apoptosis in LNCaP cells and requires hydroxyl groups to decrease viability in LNCaP and DU 145 cells

Abstract: Resveratrol was toxic to cells regardless of whether the cells were hormone-responsive or -unresponsive. This finding suggests that the cell's hormone responsive status is not an important determinant of the response to resveratrol. Furthermore, the hydroxyl-groups on resveratrol are required for cell toxicity. Finally resveratrol but not DES induced caspase-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…It has been suggested that available hydroxyl groups are important for decreasing cancer cell viability. 9 Our results seem to agree to this hypothesis, in fact the compound 5-allyl-3-nitrobenzene-1,2-diol (3) was significantly more potent than eugenol (1).Necrosis results in a disruption of cytoplasmic membrane and the necrotic cells release cytoplasmic LDH and other cytotoxic substances into the medium. We therefore examined the membrane permeability of the treated cells through the existence of LDH in their culture medium.…”
supporting
confidence: 79%
“…It has been suggested that available hydroxyl groups are important for decreasing cancer cell viability. 9 Our results seem to agree to this hypothesis, in fact the compound 5-allyl-3-nitrobenzene-1,2-diol (3) was significantly more potent than eugenol (1).Necrosis results in a disruption of cytoplasmic membrane and the necrotic cells release cytoplasmic LDH and other cytotoxic substances into the medium. We therefore examined the membrane permeability of the treated cells through the existence of LDH in their culture medium.…”
supporting
confidence: 79%
“…Similar biological effects of resveratrol have been reported in the androgen-independent prostate cancer (DU145 or PC-3; refs. 5,10,35,36) and glioma (U251; ref. 37) cell lines, which harbor constitutively-active Stat3 (33,38).…”
Section: Discussionmentioning
confidence: 99%
“…36) or in parallel with modulation of other factors, such as prostate-specific antigen (5,6,49). Previous studies also indicate that resveratrol-mediated apoptosis of breast cancer and endometrial adenocarcinoma cells may be dependent or independent of the estrogen receptor status (2, 50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has been shown to induce apoptotic cell death in a number of cancer cell lines, including hormonesensitive LNCaP prostate cells (15), hormone-insensitive DU 145 prostate cells (16), mouse myeloid leukemia cells (5), human B cell chronic leukemia cells (17), as well as several other human cancer cell lines such as MCF7, SW480, HCE7, Seg-1, and HL60 (2). Alteration of expression of Bcl-2 family of proteins, loss of mitochondrial function, release of cytochrome c, and activation of caspases may be involved in resveratrol-induced death, as shown in Bcl-2 overexpressing U937 cells (18), pancreatic carcinoma cells (19), mouse myeloid leukemia cells (5), normal and leukemic hematopoietic cells (17), and human Caco-2 colonic adenocarcinoma cells (20).…”
Section: Introductionmentioning
confidence: 99%